PENERAPAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK PADA MATERI SIFAT KOLIGATIF LARUTAN DI SMAN 2 MATARAM - Muhammad Rizal Umami; Eka Eka; Hasinah Hasinah (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
The aim of this study was to improve student activity and learning outcomes on colligative properties of solutions material at public senior High school 3 Bengkulu. This research is a classroom action research (CAR) which consists of three cycles. This research was conducted in class XII MIPA 2 public senior High school 2 Mataram. The instruments that used were observation instruments and cognitive tests. Based on the results of observations from cycle I, cycle II, and cycle III, there is an increase in the percentage of student activity and completeness of learning outcomes. The percentage of student activeness respectively was 32.37%, 55.25%, and 84.76%. Meanwhile, the percentage of student learning outcomes was 17%, 31.4% and 82.8%. The results showed that the application of the Discovery learning model succeeded in increasing student activity and learning outcomes. This can be seen from the percentage of activeness and completeness of learning outcomes that have increased by more than 75%.